Comparison And Assessment Of Methods Used To Estimate Egfr In Ckd Patients: The Role Of Clinical Pharmacist And Direct Medical Costs - Abdulla, Aljasmi Saba Mohsen Mohamed (2021)
Assessment of kidney function has dual objectives, staging of CKD and appropriate dosing of medications. Gold standard of this assessment is still urinary clearance and glomerular filtration rate. Drug dosing in chronic kidney disease (CKD) are estimated randomly by using one of the renal function equations. This study aimed to evaluate GFR estimating algorithms for medication dosing in CKD patients. Simulation of 1200 cases and 22 example of medications were conducted to evaluate the discordance of the various renal function estimated equations in medication dosing. Discordance found in dosing among 5 studied methods ranged from 20 to 40%. Pairwise eCrCl or eGFR comparisons showed that all formulas gave statistically different results (P < 0.0001) except for CG vs MDRD (P = 0.5147). Concordance ranges from as low as 55% for lamivudine (CG vs albumin– based) to 99% for enoxaparin, eptifibatide, and ranitidine (MDRD vs CKD–EPI) and dose differences in meropenem and cefepime can reach up to 37% and 42%. Moreover, Systematic review was performed by using secondary databases such as, Public/Publisher Medline (PubMed) and Elton B. Stevens Company (EBSCO), data from literature was simulated to timely quantify any potential for measurable clinical differences between Cockroft-Gault (CG) equations versus Modification of Diet in Renal Disease (MDRD). A total of 8701 patients were included with 2610 and 2631 different recommendations in simulations. Significant margin was found of about 16% for a change in mortality if CG is used versus MDRD for dosing in this study population. Gender effect on the optimal dosing was tested, resulting in no effect of gender on the discordance between the equations. A paired-proportion cohort design was applied for 195 real patients at a flagship military hospital in the United Arab Emirate. Demographics, SCr, 24 urine collection as well as past and concurrent medical history were collected. Dose adjustments to desire clinical response done by clinical pharmacist and nephrology teams and it was recorded in standardized form. Validated neural network software on the entire data set was applied. A total of 1487 concurrent medications and 785 drugs were included with renal elimination. Moreover, there were 107 changes in pharmacotherapy done by the nephrology or multidisciplinary team and 70 documented clinical pharmacy interventions.